A Segmentation Study on How Czech Consumers Make Household Food Purchases - Šárka Velčovská; Vendula Prokopová (Amfiteatru Economic, 2025)
Understanding consumer behaviour is crucial for companies operating in the food products market, which has undergone numerous changes in recent years. Consumer typology plays a vital role in the development of effective marketing strategies and in catering to diverse consumer needs. The article explores the topic of consumer behaviour in the Czech Republic when making household food purchases. It aimed to develop a consumer typology in the Czech food products market and identify differences between segments based on sociodemographic characteristics, purchasing behaviour and attitudes, including responses to current trends such as price increases and new retail technologies. Quantitative research was conducted on a representative sample of 352 respondents. Using principal component analysis and cluster analysis, five clusters were profiled, namely, the disinterested consumers, the thrifty consumers, the prepared consumers, the modern consumers, and the busy consumers. The study demonstrated how segments differ and which components primarily influence consumers in particular segments. Classifying Czech consumers based on preferences and attitudes is more valuable than traditional segmentation based on sociodemographic characteristics. It can be more useful in setting marketing targets.